Propriedades óticas e de transporte em heteroestruturas semicondutoras contendo GaMnAs - Rodrigues, Daniel Henrique (2011)
In this work, we have investigated Ga1-xMnxAs/GaAs/AlAs quantum wells (QWs) with low Mn concentration (x < 0.1%) grown by Molecular Beam Epitaxy at substrate temperatures of 400 and 450°C. We have investigated the time-resolved and polarized resolved photoluminescence as a function of laser power excitation, temperature and magnetic field for samples of 4nm and 6nm QW width. The emission spectra of the 4nm QW show two emission bands. The lower band energy presented a distinct behavior with a relatively long decay-time that may be associated to a spatial- and momentum-indirect recombination involving an electron from the AlAs layer and a hole at the GaMnAs QW. The higher energy band was associated to the direct transition in the GaMnAs QW. On the other hand, a wider, is also observed at high Mn concentration for the both QW widths. This band is due to donor-bound exciton emission from shallow donors, Mn interstitial, in the QWs. Our results show that circular polarization degree is very sensitive to the Mn concentration and QW width. In addition, we have also investigated the transport and optical properties of p-i-n AlAs/GaAs/AlAs double barrier resonant tunneling diodes (RTD) with a Ga0,95Mn0,05As top-layer contact and an InGaAs QW in the n-doped GaAs contact side. A reference sample with similar design, except that the magnetic layer was replaced by a C-doped GaAs was also investigated. The spin polarization in this samples was investigated by measuring the I(V) characteristic curves and circular-polarized electroluminescence (EL) and photoluminescence (PL) spectra as a function of the applied voltage and a magnetic field parallel to the tunneling current. We have observed clear evidence of hole resonances in the I(V) characteristic curves for both samples at 2K. The EL and PL intensities from both the GaAs and InGaAs QWs show a clear correlation with the resonances in the I(V) characteristics curves for both samples. The circular polarization degree from the GaAs and the InGaAs QWs attain large values and are more sensitive to the bias voltage in the Mn-doped sample. We have observed a polarization degree up to ~-80% for the GaAs QW emission from the magnetic RTD under 15T and 2K. Under light excitation, holes are photocreated in the non-magnetic side and injected along the structure, which strongly affects the degree of circular polarization of the carriers.